Rabdosia rubescens Linn: green synthesis of gold nanoparticles and their anticancer effects against human lung cancer cells A549 - Xi Zhang; Zhenyue Tan; Kunjing Jia; Wenzhi Zhang; Minyan Dang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Nanomedicine is a rapidly emerging field and is reported to be a promising tool for treating various diseases. Green synthesized nanoparticles are documented to possess a potent anticancer effect. Rabdosia rubescens is a Chinese plant which is also one of the components of PC-SPES and used to treat prostate cancer. In the present study, we synthesized the gold nanoparticles from R. rubescens (RR-AuNP) and analyzed its anticancer activity against the lung carcinoma A549 cell lines. Since lung cancer is reported to be with increased morbidity and decreased survival rate. The biosynthesized RR-AuNP were confirmed using UV-Visible spectrophotometer, size and shape of RR-AuNP were assessed by DLS, TEM and EDX. The biomolecules present in RR-AuNP and its topographical structure were detected using FTIR, SAED and AFM analysis. MTT assay was performed to detect the IC50 dose of RR-AuNP and its apoptotic effect was assessed by detecting the caspases activation, ROS generation. The anticancer effect of RR-AuNP was confirmed by DAPI staining, TUNEL assay and its molecular mechanism were confirmed by assessing the apoptotic signalling molecules protein expression. Our results illustrate that RR-AuNP showed a strong absorption peak at 550 nm and the RRAuNP were polydispersed nanospheres with size of 130 nm. RR-AuNP IC50 dose against A549 lung carcinoma cell line was detected to be at 25 µg/ml. The results of DAPI staining, TUNEL and immunoblotting analysis confirms both the 25 µg/ml and 50 µg/ml of RR-AuNP possess potent anticancer and apoptotic effect, suggesting that RR-AuNP that it may be a persuasive molecule to treat lung cancer.